Workforce Inclusion through Training: Evidence from Indonesia’s Disabled Labor Force - Endawansa, Althof; Setyonaluri, Diahhadi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
The employment participation gap between persons with and without disabilities in Indonesia remains pronounced, with structural and social barriers limiting equal access to decent work. This study contributes to the literature by providing robust empirical evidence on the role of job training in enhancing both overall labor force participation and formal sector employment among persons with disabilities. Drawing on nationally representative 2021 SAKERNAS data and applying logistic regression models, the analysis reveals that training significantly increases the likelihood of employment, particularly in the formal sector where social protection and job stability are more prevalent. Beyond training, the study highlights how education, gender, regional location, household characteristics, and disability type influence labor outcomes, underscoring the need for multidimensional interventions. These findings suggest that inclusive and targeted training programs, integrated with broader employment and disability policies, are essential to foster equitable labor market inclusion in Indonesia.